OPTIMAISASI PENDAPATAN PETANI PADI PADA DIVERSIFIKASI USAHA DI DESA SUKARAJA KECAMATAN BUAY MADANG KABUPATEN OGAN KOMERING ULU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
East OKU District In terms of production of paddy farmers who rely on irrigation networks many farmers in the village although it is a rainfed farmers. Due to the narrowing of farmland pengahasilan production of rice farming alone is not sufficient to meet the needs of farmers' lives and because the average in the village has two harvests in a year, so many farmers are diversifying the business to earn income outside the farming rice. Narrowing of the land and the times giving ideas to diversify its business. Business diversification is one of the main programs of agricultural development. Program development of farm diversification in paddy fields associated with efforts to increase revenues, expansion of employment opportunities and poverty reduction, is one option the right strategy. Diversification is done is diversify the types of business or agricultural crops to avoid dependence on any of the results of operations or agricultural produce as well as minimize the risk of crop failure, then other commodities will cover or reduce the loss suffered by the rice farmers. diversification of farming by the farmers in the village of Talbot namely rice farming and business diversification swallow, rice farming and business diversification fish (catfish), diversification of rice farming and vegetable farming (chickpeas) and diversification of rice farming and rubber farming. the purpose of this study was to mengnalisis